Dimensions of Trust: The Tensions and Challenges in Provider-Interpreter Trust - Hsieh, Elaine (2009)
This study problemtizes provider-interpreter trust, examining the challenges to providers' and interpreters' collaboration in bilingual health care. We conducted in-depth interviews and focus groups with 26 medical interpreters (from 17 languages) and 32 providers (from 4 specialties) in the United States to provide an empirically-based framework of provider-interpreter trust. Constant comparative analysis was used for data analysis. We identified four dimensions of trust, theoretical constructs that can strengthen or compromise provider-interpreter trust: interpreter's competence, shared goals, professional boundaries, and established patterns of collaboration. We further explore how these dimensions highlight tensions and challenges that are unique in provider-interpreter relationship. We concluded with practical guidelines that can enhance provider-interpreter trust and propose future research directions in bilingual health care.